Consumption and social identity: Evidence from India - Melanie Khamis; Nishith Prakash; Zahra Siddique (Institute for the Study of Labor (IZA), 2010)
We examine spending on consumption items which have signaling value in social interactions across groups with distinctive social identities in India, where social identities are defined by caste and religious affiliations. The classification of such items was done by eliciting responses to a survey in India. We match the results of our survey with nationally representative micro data on household consumption expenditures. We find that disadvantaged caste groups such as Other Backward Castes spend nine percent more on visible consumption than Brahmin and High Caste groups while social groups such as Muslims spend eleven percent less, after controlling for differences in permanent income and demographic composition of households. These differences are significant and robust. Additionally, we find that these differences can be partly explained as a result of the status signaling nature of such consumption items.
Keywords: D12; D70; O10; 330; households; consumption; India